La performance ininterrotta: Attori spettatori e Intelligenza Artificiale nello spazio fictional dei social media - Berlangieri, Maria Grazia (Mimesis Journal, 2023)
This paper proposes overcoming the active/passive paradigm that does not fully comprehend the complexity of the current technological context in which the spectator biosphere is immersed today. The spectator/user is engaged in an uninterrupted performance that produces digital documents thanks to the incessant nature of online communication, which is characterized by an all too underestimated fictional imprint. The notion of technology as a mere “tool” and digitisation as a mere “copy” of the real is also inadequate. The advent of digital recording and widespread archivability force human beings to take a new step in the relationship with the artificial, especially with the development of Artificial Intelligence (AI), which will determine another crucial page of the “digital turn” in the coming years. This paper focuses on two main aspects. Firstly, the macro-processes underlying the capitalization processes of what the philosopher Maurizio Ferraris defines as “documanity”. Secondly, through some “liminal” case studies, the essay examines how the roles of actors and spectators are increasingly subject to interference within social media and digital technologies, to which we now add the “rewriting of reality” by the mass diffusion of AI. While AI can be a guarantee of enormous scientific progress, if unregulated, it can also be the trigger for destructive processes and for the appropriation of cultural and artistic skills that have always been the responsibility of “human capital”. Everything passes not from the dichotomous stance that opposes humanity and artificiality but from the mature acceptance of their natural hybridity and the promotion of an active understanding of the complex phenomena of digitization, particularly in the humanities and not least in the field of performance studies.